Randomized clinical trial testing the efficacy and safety of 0.5% colchicine cream versus photodynamic therapy with methyl aminolevulinate in the treatment of skin field cancerization: Study protocol - Miola, Anna Carolina [UNESP]; Ferreira, Eliane Roio [UNESP]; Abbade, Luciana Patricia Fernandes [UNESP]; Schmitt, Juliano Vilaverde [UNESP]; Miot, Helio Amante [UNESP] (Springer Nature, 2018)
Background: The primary clinical manifestation of skin field cancerization is the presence of actinic keratoses (AKs). Current treatments for AKs related to skin field cancerization include photodynamic therapy (PDT) and colchicine. The objective of this study is to evaluate the efficacy and safety of 0.5% colchicine cream versus PDT with methyl aminolevulinate (MAL-PDT) in the treatment of skin field cancerization. Methods: In a randomized controlled and open clinical trial with a blind histopathological and immunohistochemical analysis, 36 patients with up to 10 AKs on their forearms will be included from the outpatient clinic. The forearms will be randomized into two groups, clinically evaluated and biopsied for histopathology and immunohistochemistry (p53 and Ki67). One forearm will be treated with 0.5% colchicine cream for 10 days, and the other forearm will receive one session of MAL-PDT; the forearms will subsequently be reassessed clinically and histologically after 60 days (T60) of treatment. The primary endpoint will be the point of complete clearance of AKs in T60. The sample size will enable a detection in the reduction of over 10% in AK counts between the groups with power of 0.9 and an alpha of 0.05, accounting for an estimated dropout rate of 10%, resulting in 36 patients (72 forearms). All participants included in the randomized study will be part of the analysis, and the final outcomes of any dropouts will be the value of their last visit (LOCF). The statistical analysis will be performed using SPSS 22.0, and a p value < 5% will be considered to be significant. Discussion: It is expected that colchicine will be superior to MAL-PDT in reducing AKs and in the skin field cancerization, and there will be good tolerability in both groups. Colchicine intervention is novel in that it provides a new alternative to MAL-PDT. Moreover, this drug is inexpensive that may be a potential treatment of skin field cancerization that can be prescribed in public health systems with good results.
Keywords: Actinic keratoses; Colchicine; Methyl aminolevulinate; Photodynamic therapy; Skin cancer; Skin field cancerization